Side-emission properties of femtosecond laser induced scattering centers in optical fibers - Reupert, Aaron; Heck, Maximilian; Nolte, Stefan; Wondraczek, Lothar (Optical Materials Express, 2019)
Fiber optical light diffusers that enable interstitial light delivery have become a useful tool for various illumination tasks, such as in photodynamic therapy. However, existing methods based on light diffusing fiber tips are not applicable for spatially selective light delivery in more complex structures. Here, we employ femtosecond laser induced scattering centers without mechanical manipulation and removal of the outer coatings for generating customized emission patterns. Tailoring of the cumulative emission profile is achieved through controlling the step-width between modification spots. An in-depth evaluation shows that the side-emission pattern is the result of an interplay of several scattering mechanisms that interact with cladding and core modes.
CRIS-Team Scopus Importer:2023-04-20